2020
DOI: 10.1128/msystems.00473-20
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Strategies for Survival in the Glass Sponge Vazella pourtalesii

Abstract: Few studies have explored the microbiomes of glass sponges (Hexactinellida). The present study seeks to elucidate the composition of the microbiota associated with the glass sponge Vazella pourtalesii and the functional strategies of the main symbionts. We combined microscopic approaches with metagenome-guided microbial genome reconstruction and amplicon community profiling toward this goal. Microscopic imaging revealed that the host and microbial cells appeared within dense biomass patches that are presumably… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 97 publications
(128 reference statements)
3
35
0
Order By: Relevance
“…The inclusion of the here generated genome of the thaumarchaeal symbiont from the deep-sea sponge Hymedesmia ( Stylopus ) methanophila suggests that low GC content is a general feature among deep-sea sponge-associated Thaumarchaeota. This is further supported by the recently published thaumarchaeal genomes from the deep-sea glass sponge Vazella pourtalesii , which had GC content between 31.8 and 40.4% ( Bayer et al, 2020 ). The general features of the analyzed genomes are summarized in Supplementary Table S1 .…”
Section: Resultssupporting
confidence: 66%
“…The inclusion of the here generated genome of the thaumarchaeal symbiont from the deep-sea sponge Hymedesmia ( Stylopus ) methanophila suggests that low GC content is a general feature among deep-sea sponge-associated Thaumarchaeota. This is further supported by the recently published thaumarchaeal genomes from the deep-sea glass sponge Vazella pourtalesii , which had GC content between 31.8 and 40.4% ( Bayer et al, 2020 ). The general features of the analyzed genomes are summarized in Supplementary Table S1 .…”
Section: Resultssupporting
confidence: 66%
“…Sponges are common, cosmopolitan filter feeders that pump water through their bodies to filter and ingest nutrients and microorganisms (13,14). Previous ex situ experiments have shown that sponges, including Geodia barretti (15), Tethya wilhelma (16), Halichondria panicea (17), Haliclona pigmentifera (18), and Vazella pourtalesii (19), have a high tolerance of hypoxia. For instance, T. wilhelma can maintain normal transcription at ;0.5 mM O 2 (16), despite lacking key components of the hypoxia-inducible factor (HIF) pathway, which regulates hypoxic responses in other invertebrates (16).…”
mentioning
confidence: 99%
“…Many sponge species form symbioses with Nitrosopumilus-like ammonia-oxidizing Archaea (AOA) and/or Nitrospira spp. nitrite-oxidizing Bacteria (NOB) (19,(40)(41)(42)(43)(44). Each of these prokaryotic groups utilizes sponge waste ammonia for nitrification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of the here generated genome of the thaumarchaeal symbiont from the deep-sea sponge Hymedesmia (Stylopus) methanophila suggests that low GC content is a general feature among deep-sea sponge-associated Thaumarchaeota. This is further supported by the recently published thaumarchaeal genomes from the deep-sea glass sponge Vazella pourtalesii, which had GC content between 5 https://img.jgi.doe.gov/cgi-bin/mer/main.cgi 31.8 and 40.4% (Bayer et al, 2020). The general features of the analyzed genomes are summarized in Supplementary Table S1.…”
Section: General Genomic Informationsupporting
confidence: 68%